Ventilatory and biomechanical response analysis in short vs. long interval training sessions in elite long distance swimmers - Hellard, P.; Dekerle, J.; Nesi, X.; Toussaint, J. F.; Houel, N.; Hausswirth, C. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: It is known that continuous exercises performed at the lactate threshold have the greatest effect upon the body`s oxygen transport system (Billat, 2001). This type of training enables swimmers to attain max by restoring the slow component of and by reducing the amplitude of the slow component after a period of training (Carter et al., 2000). Restoration of the slow component of appears to be more frequent among athletes having a high fractional at the lactate threshold (Billat, 2001) which is typical of ultra-endurance athletes (Billat et al., 2001). We hypothesized that in high-level long-distance swimmers, long interval training at LT, induce a large slow component of . METHODS: Seven elite male long-distance swimmers (Mean ± SD, age 21.4 ± 3.5 yrs; weight 71 ± 5 kg ; height 180 ± 5 cm) performed in a 6x300-m incremental swimming exercise to exhaustion in order to determine lactate threshold (LT = 3.1 ± 1.2 mmols/l), and the velocity. Secondly, the parameters of kinetics were calculated for the first 500m of one interval training set: 6 x 500-m using a double exponential model. RESULTS: The fit for the two-term exponential model was (r²= 0.62 ± 0.18). All seven subjects displayed a slow component of during the first 500m of IT6*500 with values measured at 401.7 ± 129.9 lO2/mn and 5.69 ± 1.96 ml/mn.kg. DISCUSSION: Elite Long-distance swimmers exhibit exceptionally high levels of peak oxygen uptake and peak swimming velocity at the lactate threshold. All of the swimmers tested exhibited a large amplitude slow component of oxygen uptake.